Ps-LAMBDA: Ambiguity success rate evaluation software for interferometric applications - Verhagen, S.; Li, Bofeng; Teunissen, Peter (Elsevier, 2013)
Integer ambiguity resolution is the process of estimating the unknown ambiguities of carrier-phase observables as integers. It applies to a wide range of interferometric applications of which Global Navigation Satellite System (GNSS) precise positioning is a prominent example. GNSS precise positioning can be accomplished anytime and anywhere on Earth, provided that the integer ambiguities of the very precise carrier-phase observables are successfully resolved. As wrongly resolved ambiguities may result in unacceptably large position errors, it is crucial that one is able to evaluate the probability of correct integer ambiguity estimation. This ambiguity success rate depends on the underlying mathematical model as well as on the integer estimation method used. In this contribution, we present the Matlab toolbox Ps-LAMBDA for the evaluation of the ambiguity success rates. It allows users to evaluate all available success rate bounds and approximations for different integer estimators. An assessment of the sharpness of the bounds and approximations is given as well. Furthermore, it is shown how the toolbox can be used to assess the integer ambiguity resolution performance for design and research purposes, so as to study for instance the impact of using different GNSS systems and/or different measurement scenarios.